The Conditions of Resilience: Families, Social Services and Social Workers Facing the COVID-19 Pandemic - Gui, Luigi; Sanfelici, Mara (Italian Sociological Review, 2022)
This article draws on empirical evidence from a study that explored the impact of the COVID-19 crisis on families and social services. During the first wave of the pandemic, an online survey was administered to Italian social workers. The aim was to give voice to the perspective of frontline professionals, analysing the transformation of families’ needs, and practices activated by social services to respond to emerging issues. Our study reveals the dynamic interplay of individual characteristics, family networks, and measures deployed by policies and social services to cope with the crisis. Through common themes that emerged from the analysis, this article shows how resilience of professionals and informal social networks can be enhanced before and after severe stressors arise, as well as the influence of organizational and structural conditions that can foster or hinder resilient responses. Social work can be strategic to anticipate critical developments, as well as to be prepared in fostering adaptive transformations, involving people and institutions in a process of collective learning. The pandemic has shown the effectiveness of more flexible and creative practices: the challenge is now to co-construct cultural and structural changes that allow incorporating them into new routines of social work practices, and to orient the renewal of welfare models and social interventions.